The cellular uptake and cytotoxic effect of curcuminoids on breast cancer cells - Chi-Chang Chang; Chi-Feng Fu; Wei-Te Yang; Tzu-Yu Chen; Yi-Chiang Hsu (Elsevier, 2012)
Objective: Curcuminoids (including curcumin) are natural antioxidants demonstrating potent chemopreventive properties against several forms of cancer. This study investigated the antiproliferative and induced apoptotic effects of curcuminoids on three cell lines isolated from human breast adenocarcinoma and ductal carcinoma (MDA-MB-231, MDA-MB-435S, and MCF-7). Materials and Methods: This study developed a highly sensitive, reproducible assay method using high-pressure liquid chromatography to quantify the cellular uptake of curcuminoids by breast cancer cells and quantitate its effect on inhibition of proliferation and activation of apoptosis in breast cancer cells. Results: Results indicate that curcuminoids inhibited cell proliferation and activation of apoptosis in the cell lines in this study. Both effects were observed to increase in proportion to the cellular uptake of curcuminoids; cellular uptake increased following an increase in the dosage of curcuminoids. Conclusion: The inhibition of proliferation and increased apoptosis of breast cancer cells appears to be associated with the uptake of curcuminoids by cancer cells.